Conceptual principles of multilingualism didactics in Germany (Pedagogy of Higher and Secondary Education, 2012)
Hamanyuk V. A. Conceptual principles of multilingualism didactics in Germany.The article deals with the main conceptual ideas of multilingualism didactics. Special attention is paid to the requirements to teaching of the native language, opportunities of using of linguistic experience and didactic principles of multilingualism as a pedagogical category.
Keywords: integrative didactics; didactics of multilingualism; language awareness; transfer of knowledge; language profiles